2022
DOI: 10.1111/1759-7714.14338
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0010235 facilitates lung cancer development and immune escape by regulating miR‐636/PDL1 axis

Abstract: Background: Circular RNAs (circRNAs) are a class of important regulators in various human cancers, including lung cancer. Here, we aimed to investigate the role of circ_0010235 in lung cancer. Methods: The expression of circ_0010235, microRNA-636 (miR-636) and PDL1 was measured by quantitative real-time PCR (qRT-PCR). Cell proliferation was evaluated by CCK-8, colony formation, and 5-ethynyl-2 0 -deoxyuridine (EdU) assays. Cell apoptosis was detected by flow cytometry. Cell invasion was assessed by transwell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Another example is bta-miR-26a which also reduced the abundance of PCK1 [44,45]. Moreover, the oncosuppressor miR-20a-3p was identified in melanoma, tongue squamous cell carcinoma, and hepatocellular carcinoma, and the oncosuppressor miR-636 was also identified in lung cancer, nasopharyngeal carcinoma, cervical cancer, endometrial cancer, ovarian cancer, and hepatocellular carcinoma [46][47][48][49][50][51][52][53][54][55][56]. It was reported that high miR-20a-3p and miR-636 expression were correlated with poor OS of CRC patients and this was consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Another example is bta-miR-26a which also reduced the abundance of PCK1 [44,45]. Moreover, the oncosuppressor miR-20a-3p was identified in melanoma, tongue squamous cell carcinoma, and hepatocellular carcinoma, and the oncosuppressor miR-636 was also identified in lung cancer, nasopharyngeal carcinoma, cervical cancer, endometrial cancer, ovarian cancer, and hepatocellular carcinoma [46][47][48][49][50][51][52][53][54][55][56]. It was reported that high miR-20a-3p and miR-636 expression were correlated with poor OS of CRC patients and this was consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, circ_0010235 knockdown can further hamper the development of NSCLC. 104 More importantly, circ_0010235 has been found to increase the expression of PD-L1 via the miR-636/PD-L1 axis. 104 Thus, such candidate can potentially provide multiple anti-cancer effects in cancer treatment.…”
Section: Circ_0010235mentioning
confidence: 99%
“…The development of NSCLC involves many molecular abnormalities and is accompanied by complex biological processes [ 8 ]. The expression of non-coding RNAs is a useful indicator to describe the molecular characteristics of NSCLC and plays a crucial role in the regulation of the immune system [ 9 , 10 ]. Many circRNAs function as oncogenic or inhibitory non-coding RNAs that participate in tumor progression and tumor immunity of NSCLC, such as circC190 and circNDUFB2 [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%